Studi Komparatif Hasil Belajar Peserta Didik yang Mengaji dan Tidak Mengaji di Madrasah Diniyah Takmiliyah Wustha dalam Mata Pelajaran Qur’an Hadits - Marlinda, Linda; Aimi, Widi (THORIQOTUNA: Jurnal Pendidikan Islam, 2025)
This study aims to compare the learning outcomes of the Qur'an Hadith between students who study and do not study the Qur'an at Madrasah Diniyah Takmiliyah Wustha (MDTW). This study focuses on the differences in learning outcomes in the Qur'an Hadith subject at school between the two groups of students. The research method used is a comparative research method through a quantitative approach with a population of 502 people. The sample in this study were 47 students in grades VII F and VII G, the sampling was obtained using a purposive random sampling technique. Data collection techniques and research instruments used were observation, documentation, and interviews. Based on the results of data processing, it was obtained that students who attended education at Madrasah Diniyah Takmiliyah Wustha (MDTW) at MTs Negeri 3 Ciamis had better learning outcomes in the Qur'an Hadith subject compared to those who did not attend education at Madrasah Diniyah Takmiliyah Wustha (MDTW). Students who study the Quran at MDTW obtained an average score of 91.48, included in the very good category, while students who did not study the Quran at MDTW obtained an average score of 88.36, included in the good category. The t-test analysis showed that the calculated t value of 2.1 was greater than the t table of 2.015 at a significance level of 5%, so the alternative hypothesis was accepted. This indicates that education at MDTW significantly contributes to better learning outcomes in the Qur'an Hadith subject. The results of this study are expected to contribute to the understanding of the influence of the activity of studying the Quran at MDTW on the learning outcomes of the Quran Hadith and provide insight into improving the learning process of the Quran Hadith subject in schools.